Effects of the School-Based Integrated Health Promotion Program With Hydroponic Planting on Green Space Use and Satisfaction, Dietary Habits, and Mental Health in Early Adolescent Students: A Feasibility Quasi-Experiment - Kwok, Stephen Wai Hang; Wu, Cynthia S. T.; Tong, Hiu Tung; Ho, Chun Ni; Leung, Ka Lee; Leung, Yolanda C. P.; Lui, Kam Chung; Wong, Carson K. C. (Frontiers in Public Health, 2021)
Background: School-based green space activities had been found beneficial to adolescent students' physical activity level and lifestyle habits. However, their effects on green space use and satisfaction, mental health and dietary behaviors required further investigation. This study aimed to investigate the effects of school-based hydroponic planting integrated with health promotion activities in improving green space use, competence and satisfaction, healthy lifestyle, mental health and health-related quality of life (QoL) among early adolescent students in secondary schools. Methods: This study adopted a three-group comparison design (one control and two intervention groups). Secondary school students (N = 553) of grade 7-9 participated in either 1) hydroponic planting (twice per week for eight months) integrated with health promotion activities; 2) only health promotion activities (once per week for six weeks); or 3) control group. Outcomes assessed by questionnaire included green space use and satisfaction, life happiness, lifestyle, depressive symptoms, and health related quality of life. Results: After adjusting for sex and school grade, the scores in "Green space distance and use" and "Green space activity and competence" were significantly better in the intervention groups than in control group. Hydroponic planting integrated with health promotion activities was also associated with better score in the dietary habits as well as resistance to substance use. Intervention groups had higher score in "Green space sense and satisfaction" and life happiness when compared with control group. Conclusions: Our study shows that the school-based hydroponic planting integrated with health promotion activities were feasible and, to a certain extent, useful to improve green space use and competence, dietary habits and resistance to substance use among early adolescent students in secondary schools in urban areas. Future studies should address the limitations identified, for example, designing randomized controlled trial which could fit school schedule to generate new evidence for physical and mental health in adolescent communities.